Tinjauan Pertimbangan Hakim Menjatuhkan Pidana Pokok dan Tambahan Dalam Perkara Melanggar Kesusilaan di Depan Orang Lain - Pindo Asmara Tungga Deva (Verstek, 2019)
This research examines the issues regarding the reason of application for Cassation against the Military ignored his judge advocate elements in the allegations in the trial in the case violated decency and reviewing about consideration Judex Juris grant petition for cassation and your imprisonment and dismissal from military service. This research is the normative legal research is both prescriptive and applied. The source of the legal materials obtained from primary and secondary legal materials. Case study into approaches to the writing of this law.Legal materials collection techniques in this research is the study of the literature. Legal material obtained is then processed using the method of deductive syllogisms. In this study, has been known to excuse the military judge advocate submits Remedy of Cassation on the basis of careful not Factie Judex in considering the elements that allegations the trial that resulted in the main Military Court judges had been wrong in applying the law in an award has freed the defendant of all charges of the military judge advocate in criminal acts of Decency in accordance with condition of article 239 paragraph (1) letter a Act No. 31 of the year 1997 concerning Military Justice explain what a true rule of law is not applied or not applied as it should be. As well as suitability Considerations Judex Juris grant reason of Cassation judge advocate of the military, the military High Court ruling cancelling, and judge themselves by stating that based on considerations of the above Supreme Court the defendant is argues has been proven legally and convincingly guilty of committing criminal acts as didakwakan by a military judge advocate in the impeachment Article 281 paragraph (2) the book of the law of criminal law Criminal Code (KUHP) saying that anyone who deliberately and in front of other people who are there are there contrary to his will, breaking decency.Keywords: Cassation, elements in the indictmen, Criminal act of Decency